Indigenous languages as predictors of understanding and accepting COVID-19 vaccines in Nigeria and South Africa - Israel Fadipe; Abiodun Salawu; Olanrewaju John Ogundeyi (Communicare)
Indigenous African languages have often suffered neglect in health development campaigns until recently. Considering the multi-faceted effects of the COVID-19 pandemic on different peoples and societies worldwide, this article argues that vaccine campaigns in African settings cannot be impactful if they are not disseminated in the indigenous African languages. The article is hinged on Salawu’s model of indigenous language for development communication, which affirms the connection between language of communication and people’s understanding of the message communicated. The study employed a survey experimental research method. Using the pool sampling technique, both online and offline questionnaires were used to survey the opinions of 191 Nigerian and 114 South African respondents in Lagos and Mafikeng, respectively, about dominant indigenous languages used for COVID-19 vaccine messages, their degree of understanding vaccine messages and their acceptance or rejection of the vaccine messages. Interview sessions were conducted with five purposively selected health communication and media experts to determine the significance of and challenges encountered in the use of indigenous African languages for COVID-19 vaccine campaigns. The quantitative data were analysed using descriptive and inferential statistical tools, such as frequency count and percentage, chi-square, percentile and logistic regression; while the qualitative data were thematically analysed. While respondents mostly identified with messages in Yoruba, Igbo, Setswana and isiZulu, a few respondents identified with a combination of languages, although these languages did not influence their acceptance of vaccines.